2022
DOI: 10.3390/brainsci12060746
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sleep Deprivation Impairs Motor Inhibition in Table Tennis Athletes: An ERP Study

Abstract: Excellent response inhibition is the basis for outstanding competitive athletic performance, and sleep may be an important factor affecting athletes’ response inhibition. This study investigates the effect of sleep deprivation on athletes’ response inhibition, and its differentiating effect on non-athlete controls’ performance, with the aim of helping athletes effectively improve their response inhibition ability through sleep pattern manipulation. Behavioral and event-related potential (ERP) data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Numerous studies have shown that SD impairs cognitive function [ 38 , 39 , 40 ], which is consistent with our research results and presents a step down with two trough periods and plateaus. The first trough period occurs within 24–48 h of SD, which causes a 20–30% decline in cognitive function.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have shown that SD impairs cognitive function [ 38 , 39 , 40 ], which is consistent with our research results and presents a step down with two trough periods and plateaus. The first trough period occurs within 24–48 h of SD, which causes a 20–30% decline in cognitive function.…”
Section: Discussionsupporting
confidence: 93%
“…However, the potential for a cognitive plateau—wherein the benefits of training plateau or diminish beyond a certain threshold ( Lampit et al, 2014 )—emerges with excessive training. Symons, Bruce & Main (2023) and Xu et al (2022) have suggested that adjustments in training frequency are necessary to sustain training effects, especially in the face of risks such as cognitive plateau (decline) and the impacts of sleep deprivation, including decreased P3 amplitude. The empirical evidence suggests that table tennis players, averaging 3–5 h of training daily, may encounter significant physical and cognitive fatigue due to the demanding nature of the sport.…”
Section: Discussionmentioning
confidence: 99%
“…The current results further reinforce previous knowledge that impaired sleep hampers cognitive inhibitory control ( 51 ), a phenomenon also highlighted in the ERP literature. For instance, research has shown a reduction in the amplitude of the P3 component on cognitive control tasks following sleep deprivation ( 76 78 ). Furthermore, research examining emotionally charged stimuli has shown enhanced amplitudes of P3/late positive complex (LPP) to negative stimuli following sleep deprivation ( 79 ).…”
Section: Discussionmentioning
confidence: 99%